Designing Bantenese EFL listening media to develop senior high school students local cultural awareness - Dina Rachmawati; Oktania Cinanti Murti (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2021)
This research was carried out to develop a prototype of a local content-based audio media for teaching listening in English as a Foreign Language (EFL) for senior high school level. The research was conducted under two research questions i.e. What are the learning needs of Senior High Schools students for EFL listening media? How was the Bantenese local content-based media for listening developed? Design based Research was employed to conduct the study. Semi-structure interview and open-ended questionnaire were conducted to collect information about the students needs for listening in EFL teaching and learning activities. To figure out how the process of media development was done, an open-ended questionnaire was administered to students and to teachers in order to assess the quality of the media. Additionally, material and media expert validations were done. Data analysis revealed that first; the students needed Bantense folk tales local content-based audio media for listening materials in EFL classrooms in order to build their local cultural awareness. Second, the audio media was developed by adopting bottom-up approach undergoing iterative processes i.e. the phases of analysis of practical problem, the phases of media development, and testing and refinement phase, and reflection phase. The development processes yielded three products i.e. teacher handbook, student handbook, and MP3 listening materials which accommodates Bantenese folk tales. In conclusion, developing a local-content based learning media aiming at developing students awareness of their local culture and identity could be done through developing a teaching and learning media that addresses the students learning needs and be in accordance with English current curriculum adopted at schools.